Modeling, analysis, and implementations of traction systems for vehicle electrification - Monteiro, Vítor Duarte Fernandes (2024)
Apprehensions concerning greenhouse gas emissions are addressed by modern societies, where the transportation sector is seen as essential influence to alleviate such effects. In fact, around the world we are assisting to an increasing adoption of electric mobility as principal substitute of traditional vehicles based on internal combustion engine. This adoption is encouraged by the industry sector, where the most relevant players are adopting more and more models of electric vehicles. This new reality is possible due to diverse factors, where power electronics technologies are one of the most relevant, and it can be contextualized in several purposes, with a special emphasis on the battery charging systems and traction systems. By analyzing both these systems, it is possible to identify a combined configuration that permits a single power system based on power electronics with dual functionalities in terms of control, namely the charging and the driving. Moreover, this possibility, identified as “unified traction and charging system”, also permits innovative operation modes used to support the power grid, mainly through the grid-to-vehicle and vehicle-to-grid modes. In addition, it also permits the slow and fast charging, resulting in a multifunctional system based in a single power system. Including all these topics, this book chapter presents detailed power electronics technologies for traction systems used in electric mobility. The main technologies are presented and explained.